2013
DOI: 10.1080/09291016.2013.787685
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time of day and partial sleep deprivation on the reaction time and the attentional capacities of the handball goalkeeper

Abstract: The aim of this study was to investigate the effects of the time of day and partial sleep deprivation on cognitive performances (i.e., attention and reaction time [RT]) of the handball goalkeeper (GK). The protocol involved 12 healthy GK volunteer males (age: 18.5 ± 1.7 years, level of experience: 8.3 ± 2.4 years, height: 1.80 ± 5.8 cm; body-mass: 79 ± 4.2 kg). They performed three cognitive tasks, i.e. the RT test, the Stroop test, and the barrage test, respectively, to evaluate the RT, the selective attentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 45 publications
0
40
1
2
Order By: Relevance
“…These variations are known as circadian or diurnal rhythms (Cappaert 1999;Chtourou et al 2012). Circadian rhythms are present in several elements of sensorimotor, psychomotor, perceptual, and cognitive function (Jarraya et al 2013;Jarraya, Jarraya, Chtourou, et al 2014). Cognitive performances, on which coordination performances are based, are adversely affected by sleep loss (Van Dongen & Dinges 2005;Akerstedt 2007) and time since waking (Waterhouse 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These variations are known as circadian or diurnal rhythms (Cappaert 1999;Chtourou et al 2012). Circadian rhythms are present in several elements of sensorimotor, psychomotor, perceptual, and cognitive function (Jarraya et al 2013;Jarraya, Jarraya, Chtourou, et al 2014). Cognitive performances, on which coordination performances are based, are adversely affected by sleep loss (Van Dongen & Dinges 2005;Akerstedt 2007) and time since waking (Waterhouse 2010).…”
mentioning
confidence: 99%
“…Likewise, cognitive performance (i.e. simple and choice reaction times, mental arithmetic, and alertness) are time-of-day dependent, with better outcomes observed around the peak of the core temperature, as observed by Jarraya et al 2013, andJarraya, Jarraya, Chtourou, et al 2014. However, most studies report that the peak of cognitive performances is observed before the acrophase of core temperature (Van Dongen & Dinges 2000;Raichle et al 2001;Blatter & Cajochen 2007;Waterhouse 2010).…”
mentioning
confidence: 99%
“…At this time, our results showed an important peak of the body temperature. Similarly, the optimum of the reaction time was observed at the early evening near the peak of the body temperature [9,10,38,39]. It has been found that performances for strength and power in children improved significantly from morning to the afternoon [45].…”
Section: Discussionmentioning
confidence: 98%
“…In fact, this sensory integration needs a high level of vigilance, particularly when one of the sensory inputs is no longer effective [8]. Recently, it has been found that attentional capacities in trained adults are time-of-day dependent, with the best values observed in the afternoon for reaction time [9,10]. Physiology & Behavior 142 (2015) [146][147][148][149][150][151] Several studies have reported that postural control is influenced by the time-of-day [6,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in this topic reported that the disruption of the sleep-wake cycle, which is one of the main biological circadian rhythms, has various consequences on cognitive and physical performance (Davenne, 2009;Souissi et al, 2012;Jarraya et al, 2014). Although the literature is not consistent about the effect of sleep loss on physical performance (Symons et al, 1988;Souissi et al, 2003Souissi et al, , 2008Souissi et al, , 2013HajSalem et al, 2013), it was widely demonstrated that sleep loss affects cognitive functions such as attention (Goel et al, 2013), reaction time (Corsi-Cabrera et al, 1996;Jarraya et al, 2014), alertness (Doran et al, 2001), working memory, abstraction, and decision making (Diekelmann and Born, 2010;Lim and Dinges, 2010). Therefore, psychological states were affected by the sleep disruption (Kaida and Niki, 2014;Short and Louca, 2015) as previously indicated using the profile of mood states (POMS) questionnaire (e.g.…”
Section: Introductionmentioning
confidence: 99%